DELTEX E3 ligases ubiquitylate ADP-ribosyl modification on protein substrates - Zhu, K; Suskiewicz, MJ; Hloušek-Kasun, A; Meudal, H; Mikoč, A; Aucagne, V; Ahel, D; Ahel, I (American Association for the Advancement of Science, 2022)
Ubiquitylation had been considered limited to protein lysine residues, but other substrates have recently emerged. Here, we show that DELTEX E3 ligases specifically target the 3' hydroxyl of the adenosine diphosphate (ADP)-ribosyl moiety that can be linked to a protein, thus generating a hybrid ADP-ribosyl-ubiquitin modification. Unlike other known hydroxyl-specific E3s, which proceed via a covalent E3~ubiqutin intermediate, DELTEX enzymes are RING E3s that stimulate a direct ubiquitin transfer from E2~ubiquitin onto a substrate. However, DELTEXes follow a previously unidentified paradigm for RING E3s, whereby the ligase not only forms a scaffold but also provides catalytic residues to activate the acceptor. Comparative analysis of known hydroxyl-ubiquitylating active sites points to the recurring use of a catalytic histidine residue, which, in DELTEX E3s, is potentiated by a glutamate in a catalytic triad-like manner. In addition, we determined the hydrolase specificity profile of this modification, identifying human and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) enzymes that could reverse it in cells.